2018
DOI: 10.1038/s41598-018-28310-3
|View full text |Cite
|
Sign up to set email alerts
|

N-doped catalytic graphitized hard carbon for high-performance lithium/sodium-ion batteries

Abstract: Hard carbon attracts wide attentions as the anode for high-energy rechargeable batteries due to its low cost and high theoretical capacities. However, the intrinsically disordered microstructure gives it poor electrical conductivity and unsatisfactory rate performance. Here we report a facile synthesis of N-doped graphitized hard carbon via a simple carbonization and activation of a urea-soaked self-crosslinked Co-alginate for the high-performance anode of lithium/sodium-ion batteries. Owing to the catalytic g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
62
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 61 publications
4
62
1
Order By: Relevance
“…[20] The specific surfacea rea of the NCL@GF wasr ecorded up to 277 m 2 g À1 by Brunauer-Emmett-Teller (BET) method, which markedly contrasted thato fG F(% 179 m 2 g À1 )a nd NCF-GF (57 m 2 g À1 )( FigureS2b). [23] The charge-discharge profiles of the 1st, 2nd, 100th, 150th and 200th cycles of the NCL@GF electrode at acurrent density of 0.1 Ag À1 were shown in Figure 4b,w hich were similart ot hose previously reported for N-doped carbon materials. 2) The more defects were introduced to the graphene surface after the PI polymer layers converted to the carbonw ith pyrolysis.…”
Section: Resultssupporting
confidence: 78%
See 4 more Smart Citations
“…[20] The specific surfacea rea of the NCL@GF wasr ecorded up to 277 m 2 g À1 by Brunauer-Emmett-Teller (BET) method, which markedly contrasted thato fG F(% 179 m 2 g À1 )a nd NCF-GF (57 m 2 g À1 )( FigureS2b). [23] The charge-discharge profiles of the 1st, 2nd, 100th, 150th and 200th cycles of the NCL@GF electrode at acurrent density of 0.1 Ag À1 were shown in Figure 4b,w hich were similart ot hose previously reported for N-doped carbon materials. 2) The more defects were introduced to the graphene surface after the PI polymer layers converted to the carbonw ith pyrolysis.…”
Section: Resultssupporting
confidence: 78%
“…[6,21] In contrast, only the broad peak at ca. [23] It was furtherdemonstrated by Raman spectra of the NC@GF-T with visible Da nd Gb ands at about 1330 and 1600cm À1 ,r espectively ( Figure S2 a). [6,22] These results indicated that the PI had been successfully converted to amorphous after carbona nnealing process 23 .T his finding was further elucidated by the Fouriert ransform infrared (FTIR) spectra of the composites before anda fter carbonization treatment ( Figure 3b).…”
Section: Resultsmentioning
confidence: 75%
See 3 more Smart Citations